Model E-WoM dan Perceived Value Dalam Meningkatkan E-Repurchase Intention Dengan Mediasi E-Trust - Hartanto, Prasetyo; Laij, Fransisca (Jurnal Manajerial, 2024)
Background – The Covid-19 pandemic and social restrictions have spurred the growth of e-commerce in Indonesia, impacting consumer behavior and the industry, as evidenced by Shopee's success in sustaining online repurchase intentions. Aim – The purpose of this study is to analyze the relationship between various factors E-Wom, Perceived Value, and E-Repurchase Intention mediated by the E-Trust variable. Design/ Methodology/ Approach – The type of this research is descriptive verificative, and the method used is an explanatory survey with random sampling technique, involving a sample size of 174 Shopee app users. The data analysis technique employed is path analysis, utilizing IBM SPSS software version 26.0. Findings – The statistical analysis results revealed a positive and significant influence of the variables e-wom and perceived value on e-repurchase intention through the mediation of the e-trust variable, both partially and simultaneously. Conclusion - E-trust is responsible for the purchase of E-repurchase intentions. Research Implication – This study aims to contribute to management science, particularly in the fields of marketing management and the e-commerce industry, focusing on Electronic Word of Mouth, electronic trust, perceived value, and repurchase intention. It is hoped that this research can assist the e-commerce industry, such as Shopee, in developing more effective and efficient marketing strategies to enhance customer loyalty and ensure sustainable growth. Limitations – Due to the limitations of the study, the author suggests that future researchers add other variables that could enhance e-repurchase intention.